Right Information, Right Care, Right Patient, Right Time: Community Preferences to Inform a Self-Management Support Tool for Upper Respiratory Symptoms - Gutnick, Damara; Lutz, Carlo; Mani, Kyle A.; Weldon, Christine B.; Trosman, Julia R.; Rapkin, Bruce; Jinnett, Kimberly; Fleurimont, Judes; Kaur, Savneet; Jariwala, Sunit P. (Applied Clinical Informatics, 2025)
Objectives During and since the coronavirus disease 2019 (COVID-19) pandemic, communities have needed to cope with several conditions that cause similar upper respiratory symptoms but are managed differently. We describe community reactions to a self-management toolkit for patients with upper respiratory symptoms to inform mobile e-health app development. The toolkit is based on the “4R” (Right Information, Right Care, Right Patient, Right Time) care planning and management model.Methods The 4R Cold, Flu, and COVID-19 Information Tool (4R-Toolkit) along with a brief evaluation survey were distributed in three ways: through a Bronx NY Allergy/Asthma clinic, through the Bronx Borough President's Office listserv, and through peer recruitment. The survey assessed respondents' perceptions of the 4R-Toolkit's accessibility, preferences for sharing symptoms with clinicians, social media use, and e-health literacy.Results We obtained a diverse sample of 106 Bronx residents, with 83% reporting personal or a social contact with symptoms suggestive of COVID-19. Respondents varied in the information sources they preferred: computer (39%), smartphone (28%), paper (11%), and no preference (22%). Most (67%) reported that social media had at least some impact on their health care decisions. Regardless of media preferences, respondents were positive about the 4R-Toolkit. Out of 106 respondents, 91% believed the 4R-Toolkit would help people self-manage upper respiratory symptoms and 85% found it easy to understand. Respondents strongly endorsed retention of all 4R-Toolkit content domains with 81% indicating that they would be willing to share symptoms with providers using a 4R-Toolkit smartphone app.Conclusion The 4R-Toolkit can offer patients and community members accurate and up-to-date information on COVID-19, the common cold, and the flu. The user-friendly tool is accessible to diverse individuals, including those with limited e-health literacy. It has potential to support self-management of upper respiratory symptoms and promote patient engagement with providers.
Keywords: COVID-19; infectious disease; domain; clinical care; 4R-tool; eHealth; respiratory; literacy